ANALISIS PERCEPATAN PENCAPAIAN TARGET RETRIBUSI PELAYANAN PERSAMPAHAN DENGAN PEMBERIAN REWARD OLEH PIHAK KETIGA - Roy Haris Oktabian (Jurnal Ilmiah Wahana Bhakti Praja, 2020)
ABSTRACT. This activity is a new breakthrough in order to achieve the target of waste service levies that are charged to Koba District in Central Bangka Regency each year. With this activity, the City District as an agency that is authorized to levies levies, creates a new method of levies, namely by providing rewards. Reward is given to object levies who are willing to pay fees for waste services at least 2 (two) consecutive months. With this method, in addition to accelerating the achievement of targets, it is expected to be able to raise awareness and the willingness of the community to pay waste service levies so that the object of levies can increase and targets and achievements in the coming years will also increase. If this can be realized, then the Koba District Agency is considered to have provided support for the achievement of the Local Revenue targets, especially the regional levies sector. Key words : Waste Service, reward,achievement acceleration